PENGARUH CAIRAN PERASAN BEBERAPA JENIS DAUN TERHADAP PERTUMBUHAN CENDAWAN ENDOFIT Trichoderma Sp. SECARA INVITRO - Rina Sriwati, Susanna, Putri Yuni (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2012)
The study, aimed at investigating effects of several types of leaf juice liquids on growth of endophytic fungi Trichoderma sp. in vitro has been carried out in Laboratory of Plant Pathology, Faculty of Agriculture Unsyiah, Banda Aceh. The study started with preparation of liquids squeezed from leaves of four types of plant: cocoa leaf, maranggo tree, neem, and lead tree. Experiment used a completely randomized design non faktorial, consisted of 5 treatments and 4 replications. Variables measured were incubation period of spores, spore colony diameter, spore color, and spore number. Results showed that treatment of several types of leaf juice liquid exerted a highly significant effect on incubation period and spore colony diameter of fungi Trichoderma sp. The fastest incubation period (2.25 days) and the longest colony diameter (9.00 cm) were found at juice liquid of lead tree leaves. The longest incubation period (3:53 today) was found at cocoa leaf juice likuid, while the shortest colony diameter (4.98 cm) was found at juice of maranggo tree leaves. Use of all liquid leaves in various media did not affect spore numbers, although the media with juice of lead tree leave had more Trichoderma sp. than that of other media.